PENGARUH TEKNIK PENGOLAHAN TERHADAP KUALITAS KERUPUK SALA LAUAK - Melly, Melly; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study is based on the lack of saltwater consumption in innovating food, whereas many salted fish have nutritional content including protein, energy, and calcium. This study aims to analyze the effect of processing techniques on color quality, aroma, taste, and texture on cracker Sala Lauak. This research is experiment using quantitative approach, object in this research is cracker Sala Lauak by using different processing technique. Technique of collecting data using questionnaires and then crackers sala side dish on top of 30 panelists then in analysis using Duncan test. The result of this research is the influence of the dough which is directly fried, dried oven then fried and dried with the sun then fried to the form of Sala Lauak cracker produced, has the effect of dough which is directly fried, oven dried and then dried with the sun then fried on the color of cracker Sala Lauak which is produced, there is the influence of dough that is directly fried, oven dried and then fried and dried with the sun and then fried to the aroma of Sala Lauak crackers produced, there is the influence of the dough directly fried, oven dried and then dried with the sun then fried to taste crackers Sala Lauak which resulted there is the influence of dough that directly fried, oven dried and then fried and dried with the sun and then fried to the texture of crackers Sala Lauak produced.